The reporting quality of acupuncture-related traumatic adverse events: a systematic review of case studies in Korea - Sung-A Kim; Ji-Su Lee; Tae-Hun Kim; Seunghoon Lee; Jae-Dong Lee; Jung Won Kang (BMC, 2024)
Abstract Background Acupuncture is known for a harmless treatment when administered by well-trained clinicians. However, multiple case reports of traumatic adverse events (AEs) related to acupuncture treatments continue to be published in literature. In this review, we evaluated the reporting quality and conducted causality assessments of case studies that have reported acupuncture-related traumatic AEs in Korea. Methods Eight databases were searched from their inception to January 2024. Only Korean case studies that reported traumatic AEs following acupuncture procedures were included without any language restrictions. Reporting quality was evaluated based on patient characteristics, AEs, and acupuncture practice. Causality was assessed using the modified WHO-UMC causality criteria. Results Twenty-eight studies were included from a total of 1,154 identified studies. The quality of reporting in the included studies was low overall. While the descriptions of patient characteristics and AEs were relatively well detailed, most information on acupuncture practice was not reported at all. During the causality assessment, only three (10.7%) studies were judged to be "certain". Twelve (42.9%) studies were "unassessable" because they inadequately described the information necessary for decision-making. It was practically difficult to establish the causality between acupuncture and AEs, as well as the appropriateness of acupuncture practice. Conclusions Insufficient and inappropriate reporting was observed in most case studies reporting acupuncture-related traumatic AEs in Korea. To overcome these limitations, we have suggested tentative guidelines in the form of a set of items that should be reported by future authors who plan to publish case studies on acupuncture-related traumatic AEs in a clinical setting.